Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1182/blood-2005-06-2235
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-positive platelet transfusion in neonatal alloimmune thrombocytopenia (NAIT)

Abstract: Neonatal alloimmune thrombocytopenia (NAIT) is a fetomaternal incompatibility most commonly induced by maternal anti-HPA-1a, IgG alloantibodies against a polymorphic epitope of the glycoprotein IIb/ IIIa complex in approximately 97.5% of white patients. Current guidelines recommend transfusion of immunologically compatible platelets to prevent cerebral hemorrhage, the most severe complication in affected newborns. Such platelet concentrates, however, are often not readily available. In a retrospective analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 20 publications
0
69
0
7
Order By: Relevance
“…(2, 40) may be more efficient than fetal platelet transfusion. Platelet transfusion, however, may be critical to controlling bleeding after birth, as suggested from both clinical and animal studies (1,3,17,62). These findings may shift the prevailing view and advance our understanding of the pathogenesis of FNAIT and may contribute markedly to improvements in the clinical management of this life-threatening disease.…”
Section: Detection Of Anti-β3 or Anti-gpibα Antibodies Via Flow Cytommentioning
confidence: 95%
“…(2, 40) may be more efficient than fetal platelet transfusion. Platelet transfusion, however, may be critical to controlling bleeding after birth, as suggested from both clinical and animal studies (1,3,17,62). These findings may shift the prevailing view and advance our understanding of the pathogenesis of FNAIT and may contribute markedly to improvements in the clinical management of this life-threatening disease.…”
Section: Detection Of Anti-β3 or Anti-gpibα Antibodies Via Flow Cytommentioning
confidence: 95%
“…1,2 Specific regions of the gene tend to be most commonly mutated: (1) in-frame insertions in the basic/leucine zipper (bZIP) region and (2) truncating out-of-frame insertions or deletions in the N-terminus. 1,2 Although mutations are most frequently found in these 2 regions, other abnormalities have been described as well. 2 Fröhling et al reported in 6 of 236 AML cases the existence of an in-frame insertion mutation of 6 nucleotides.…”
Section: To the Editormentioning
confidence: 99%
“…4,8 After delivery, FNAIT can be treated by platelet transfusion. 9,10 However, in almost 50% of affected cases, intracranial hemorrhage occurs before delivery, sometimes as early as in the 20th week of gestation. 8,11,12 This makes antenatal treatment essential to avoid deleterious consequences.…”
Section: Introductionmentioning
confidence: 99%